Influence of Deposition Conditions on Characteristics of Fullerenes Containing Carbonic Coatings Obtained Using High-Power Ion Beams; Известия вузов. Физика; Т. 49, № 8 - Struts V. K.; Matvienko V. M.; Petrov A.V.; Ryabchikov A. I. Aleksandr Ilyich; Usov Y. P. Yuri Petrovich; Naiden E. P.; Renk T. J.; Fortuna S. V. (2006, 2006)
А possibility of obtaining thin carbon films with high content of fullerene mixture С60 and С70 using the method of sputtering graphite targets by high power pulsed ion beams (HPIBs) is shown. Investigation of films structural and phase composition was performed by the methods of transmission electron microscopy (TEM) and X ray diffraction analysis (XRDA). It is shown that the formation of fullerenes depends on the parameters defining the conditions of carbon vapor condensation in a scattering vapor plasma jet.Optimal conditions for target sputtering are defined and a possibility of controlling the composition and amount of fullerenes in films is demonstrated.